Proposal for teaching tasks to encourage environmental education in the teaching process - learning chemistry in higher secondary education - de Villa Amil Sellés, Yissel Pérez; Puerta Díaz, Lázara; Rosa del Campo, Carlos Manuel (Revista Minerva, 2023)
This article outlines the results of the research carried out as part of the training process in undergraduate studies and responds to the need to achieve the comprehensive training of young generations. It addresses the main insufficiencies detected, due to the application of methods and instruments in the environmental education of students in the municipality of Lajas in the province of Cienfuegos, Cuba. From the above, results are reflected such as that 30% of the students denote in their modes of action poor mastery of the main environmental problems of the community and the school environment, in the classes there is little connection between the contents they receive in the classroom. Chemistry subject and daily activity and little participation in activities dedicated to environmental protection. For this purpose, teaching activities were designed and applied to promote environmental education with a participatory and community nature, from the Chemistry classes, at the IPU Frank País García. The results are concrete, in that 95.4% of the students present a better command of environmental problems and suggest ways of solution as an active subject of society. 100% participate in school and extracurricular activities aimed at the conservation and protection of the environment. 63% of them feel motivated by the subject of Chemistry when the content is linked to essential aspects of environmental education, which is reflected in the increase in student participation in contests.